Pembuatan Aplikasi Penyimpanan Password Menggunakan Metode Honey Encryption Pada Android - Nouchka Indra Dewa; Agustinus Noertjahyana; Andreas Handojo (Jurnal Infra, 2022)
Currently, this data storage certainly really needs security to avoid risks such as hacker attacks, data leaks, or loss that is always there. One measure for this security is to use a password to protect the information. However, this is quite risky where passwords that have difficult combinations will be difficult to remember. To help android smartphone users in storing and securing these passwords in their smartphones, a password storage application was made. This application is made on an android smartphone using a cryptographic method, namely the Honey Encryption method. Where is an application on an Android-based smartphone that aims to store and secure passwords. Users can manually set the key that will be used in the encryption process. This encryption process is done online so that the user can make a request from the server for the key data. This online step can make it easier for users to delete and manage online backup data in the form of keys and text data for their username and password. The results of this study indicate that this system is protected by the Honey Encryption Algorithm which is able to secure the stored passwords. It also shows that this system has successfully implemented the Honey Encryption Algorithm to trick users who do not have a password by displaying the wrong password.